Newborn Screening for Mitochondrial Carnitine-Acylcarnitine Cycle Disorders in Zhejiang Province, China - Zhou, Duo; Cheng, Yi; Yin, Xiaoshan; Miao, Haixia; Hu, Zhenzhen; Yang, Jianbin; Zhang, Yu; Wu, Benqing; Huang, Xinwen (Frontiers in Genetics, 2022)
Mitochondrial Carnitine-Acylcarnitine Cycle disorders are a heterogeneous group of hereditary diseases of fatty acid mitochondrial β-oxidation tested within NBS program in Zhejiang province, China. In that case, the aim of this study was to explain the incidence, biochemical, clinical, and genetic characteristics of Mitochondrial Carnitine-Acylcarnitine Cycle Disorders discovered by NBS. From January 2009 to June 2021, a total number of 4,070,375 newborns were screened by tandem mass spectrometry. Newborns with elevated C0 levels and/or C0/(C16+C18) ratios were recalled as CPT1D, while newborns with decreased C0 levels and/or C0/(C16+C18) ratios and/or elevated C12-C18:1 levels were recalled for CPT2D or CACTD. Suspected positive patients were further subjected under genetic analysis. All confirmed patients accepted biochemical, nutritional treatment, as well as follow-up sessions. There were 20patients (12 CPT1D, 4 CPT2D, 4 CACTD) with Mitochondrial Carnitine-Acylcarnitine Cycle Disorders were diagnosed by NBS. The overall incidence of these disorders was 1 in 203,518 newborns. There were 11patients with CPT1D exhibited increased C0 levels and C0/(C16+C18) ratios. Among patients of CPT2D, all long chain acylcarnitines levels were elevated except case14 with normal C12 levels. Among patients of CACTD, all long chain acylcarnitines levels were elevated except case17 with normal C12, C18, C18:1 levels. Most patients with CPT1D were asymptomatic. Among 4 patients with CPT2D, 2of them did not present any clinical symptom, but the other 2patients were died. Among 4 cases with CACTD were onset after birth and 75% of patients died. There were 14 distinct mutations were identified in CPT1A gene of which 11 were novel and c.1910C>A (p.S637T), c.740C＞T (p.P247L), c.1328T>C (p.L443P) were the most common mutations. There were 3 novel mutations were identified in CPT2 gene, and the most frequent mutation was c.1711C>A (p.P571T). The most common variant in SLC25A20 gene was c.199-10T > G.Mitochondrial Carnitine-Acylcarnitine Cycle Disorders can be detected by NBS, and the combined incidence of newborns was rare in Zhejiang province, China. Most patients presented typical acylcarnitine profiles. Most patients with CPT1D presented normal growth and development while patients with CPT2D/CACTD showed a high mortality rate. Several novel CPT1A variants and CPT2 variants were identified, which expanded the variant spectrum.